TALAK DAN IDDAH DALAM PERSPEKTIF AL-QUR'AN DAN HADIS - Hasanudin Hasanudin (Al Hakam : The Indonesian Journal of Islamic Family Law and Gender Issues, 2021)
Divorce and iddah as the two parts described in Islam, of course, have obtained legality by syara '. The basis for the legal requirements for divorce and iddah is contained in the Koran and Sunnah, and has been agreed upon by the Ulama in the form of ijma 'on its legality. Divorce is a narrow "emergency exit". Also divorce (talak) is the only thing that is permitted but hates Allah SWT. Because; first, talak cancels the sacred marriage ties that have been termed by the Koran with "mîthâqan ghalîza". Second, talak is permissible as a form of Islamic respect for humans. Iddah is the name of a certain waiting period for a woman to find out the emptiness of her uterus. The emptiness can be identified by birth, by months, or by counting quru '(holy time). This is intended to ensure the presence or absence of pregnancy in a divorced wife, especially in the case of 'iddah divorce, iddah is intended to provide the possibility of reconciliation to the wife. Also no less important is the function of the iddah is ta'abbud which cannot be changed with the development of science and technology (IPTEK).